If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(2T + 6) = -14 Reorder the terms: -7(6 + 2T) = -14 (6 * -7 + 2T * -7) = -14 (-42 + -14T) = -14 Solving -42 + -14T = -14 Solving for variable 'T'. Move all terms containing T to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 42 + -14T = -14 + 42 Combine like terms: -42 + 42 = 0 0 + -14T = -14 + 42 -14T = -14 + 42 Combine like terms: -14 + 42 = 28 -14T = 28 Divide each side by '-14'. T = -2 Simplifying T = -2
| 0.4x-14=20 | | 6x+y=zforx | | 4(F-7)=24 | | 2xy-7y=5 | | -8(S+4)=-12 | | 13s-3=10 | | x+54+x+82+56=180 | | -4(n+7)+1=-4n-23 | | 150=4(6*5)+2(6h) | | bx+a=ab | | 7x+14=3x+34 | | 2x-7=-6X+17 | | 4(4S+2)=136 | | (6+y)-Y=6 | | .5x+1=-.67+15 | | 6x^2+24x=42 | | 3y-3-5y=3-2y | | 4n-5=6 | | -7m-4m=22 | | 150=4(6*4)+2(6h) | | l+8=26 | | f*-2=2*-2+5 | | sin(x)=1.22 | | w-8=106 | | 5x+3=5x-10+77 | | -3(5+7x)=-40+4x | | 12+6m=7m-6(m-2) | | r+4=15 | | 0=2.4x^2+4.2x+1.2 | | 18.75+x=26.55 | | 4x-8=5x+5+75 | | 6x-2x+60= |